Association between the Charlson comorbidity index and outcomes after implantable cardioverter defibrillator generator replacement. Issue 9 (6th August 2019) - Amin, Mustapha M.; Witt, Chance M.; Waks, Jonathan W.; Mehta, Ramila A.; Friedman, Paul A.; Kramer, Daniel B.; Buxton, Alfred E.; Mulpuru, Siva K.; Hodge, David O.; Frey, Rebecca J.; Frederick, Nicolette K.; Cha, Yong‐Mei; et al.
Abstract: Background: Recipients of implantable cardioverter defibrillator (ICD) generator replacement with multiple medical comorbidities may be at higher risk of adverse outcomes that attenuate the benefit of ICD replacement. The aim of this investigation was to study the association between the Charlson comorbidity index (CCI) and outcomes after ICD generator replacement. Methods: All patients undergoing first ICD generator replacement at Mayo Clinic, Rochester and Beth Israel Deaconess Medical Center, Boston between 2001 and 2011 were identified. Outcomes included: (a) all‐cause mortality, (b) appropriate ICD therapy, and (c) death prior to appropriate therapy. Multivariable Cox regression analysis was performed to assess association between CCI and outcomes. Results: We identified 1421 patients with mean age of 69.6 ± 12.1 years, 81% male and median (range) CCI of 3 (0‐18). During a mean follow‐up of 3.9 ± 3 years, 52% of patients died, 30.6% experienced an appropriate therapy, and 23.6% died without experiencing an appropriate therapy. In multivariable analysis, higher CCI score was associated with increased all‐cause mortality (Hazard ratio, HR 1.10 [1.06‐1.13] per 1 point increase in CCI, P  < .001), death without prior appropriate therapy (HR 1.11 [1.07‐1.15], P  < .0001), but not associated with appropriate therapy (HR 1.01 [0.97‐1.05], P  = .53). Patients with CCI ≥5 had an annual risk of death of 12.2% compared to 8.7% annual rate of appropriate therapy. Conclusions: CCI is predictive of mortality following ICD generator replacement. The benefit of ICD replacement in patients with CCI score ≥5 should be investigated in prospective studies.